An electrophysiological study of Congenital Mirror Movements. Issue 1 (January 2019) - Terranova, C.; Brigandı̀, A.; Allegra, C.; Rizzo, V.; Ielo, C.; Morgante, F.; Girlanda, P.
Abstract : Congenital mirror movements (CMM) are a curious and rare neurological disorder in which volitional movements of a limb are accompanied by simultaneous involuntary symmetrical movements in the contralateral one. We performed an electrophysiological study of a young man with CMM. Our patient had bilateral CMM, graded 3 on the Wood and Teuber scale. Transcranial magnetic stimulation (TMS) was performed on the left and right motor cortex (M1). Surface EMG - was obtained by the right and left FSD and ECD muscles at rest and when performing self-paced repetitive flexion–extension of the fingers. Moreover we obtained a map of M1 using an MRI-navigated transcranial magnetic stimulation device (nTMS). Bilateral motor evocated potentials (MEPs) were recorded from FDI muscles when stimulating each M1. The mean ipsilateral MEP amplitude when stimulating the left M1 was higher than the contralateral one. The surface-EMG recording mirrored the clinical findings, demonstrating simultaneous bilateral bursts of EMG activity when performing unilateral flexion or extension movements. Ipsilateral and contralateral motor area maps, obtained with nTMS, were comparable. Our finding confirm that ipsilateral and contralateral MEPs are originated in the same cortical areas. Moreover, this is the first reported navigated TMS brain mapping of patient affected by CMM.